Organization of the Zone of Transition between the Pretectum and the Thalamus, with Emphasis on the Pretectothalamic Lamina - Márquez-Legorreta, Emmanuel; Horta-Júnior, José de Anchieta C.; Berrebi, Albert S.; Saldaña, Enrique (Frontiers in Neuroanatomy, 2016)
The zone of transition between the pretectum, derived from prosomere 1, and the thalamus, derived from prosomere 2, is structurally complex and its understanding has been hampered by cytoarchitectural and terminological confusion. Herein, using a battery of complementary morphological approaches, including cytoarchitecture, myeloarchitecture and the expression of molecular markers, we pinpoint the features or combination of features that best characterize each nucleus of the pretectothalamic transitional zone of the rat. Our results reveal useful morphological criteria to identify and delineate, with unprecedented precision, several [mostly auditory] nuclei of the posterior group of the thalamus, namely the pretectothalamic lamina (PTL; formerly known as the posterior limitans nucleus), the medial division of the medial geniculate body (MGBm), the suprageniculate nucleus (SG), and the ethmoid, posterior triangular and posterior nuclei of the thalamus. The PTL is a sparsely-celled and fiber rich flattened nucleus apposed to the lateral surface of the anterior pretectal nucleus that marks the border between the pretectum and the thalamus; this structure stains selectively with the Wisteria floribunda agglutinin (WFA), and is essentially immunonegative for the calcium binding protein parvalbumin. The MGBm, located medial to the ventral division of the medial geniculate body, can be unequivocally identified by the large size of many of its neurons, its dark immunostaining for parvalbumin, and its rather selective staining for WFA. The SG, which extends for a considerable caudorostral distance and deviates progressively from the MGB, is characterized by its peculiar cytoarchitecture, the paucity of myelinated fibers, and the conspicuous absence of staining for calretinin; indeed, in many calretinin-stained sections, the SG stands out as a blank spot. Because most of these nuclei are small and show unique anatomical relationships, the information provided in this article will facilitate the interpretation of the results of experimental manipulations aimed at the auditory thalamus and improve the design of future investigations. Moreover, the previously neglected proximity between the MGBm and the caudal region of the scarcely known PTL raises the possibility that certain features or roles traditionally attributed to the MGBm may actually belong to the PTL.